EVALUASI KESESUAIAN LAHAN UNTUK PENGEMBANGAN TANAMAN KOPI ROBUSTA (Coffea canephora) BERDASARKAN ANALISIS DATA IKLIM MENGGUNAKAN APLIKASI SISTEM INFORMASI GEOGRAFI - Kandari, Aminudin Mane; Safuan, La Ode; Amsil, LM (Jurnal Agroteknos, 2013)
The aim of the study was to determine the climate type, spatially climate distribution and climate suitability class for robusta coffee crop in the district of Buton. The research was conducted in March to Agsutus 2013 by using Thiessen polygon approach through GIS spatial analyst and climate unit obtained from overlay climate elements, namely temperature, precipitation, humidity, and dry months. Research found that, in Buton, climate type according to the classification Schmidth - Fergusson climate type C in the coverage area of the station rainfall Lawele and Betoambari, and the type climate in the region of Kapontori and Kaisabu rainfall stations based on. Thiessen polygon, the widest distribution was 4 months dry climate, i.e. : 124.257,29 hectares or 59,16 % of the rainfall stations Kapontori, Kaisabu, and Betoambari. While the widest climatology element (temperature, humidity, radiation, and evaporation) were in the climatology station Kapontori : 123.240,42 ha or 58,68 % of the total study area. Actual climatic suitability classes in the study site for the coffee plants were class S2 ( quite appropriate ) area of 69.581,56 hectares or 61,46 % and marginally suitable ( S3 ) area of 43.632,03 hectares or 38,54 % with the toughest obstacles were temperature (t) and humidity (w3). While the potential climatic suitability remained on climate spesific class S2 (quite appropriate) and S3 (marginally suitable). With the results of the evaluation of the climatic suitability , coffee plants can be developed in the research area. Keywords: climate, coffee, land suitability